2014
DOI: 10.1007/s00280-014-2379-y
|View full text |Cite|
|
Sign up to set email alerts
|

shRNA-mediated silencing of ZFX attenuated the proliferation of breast cancer cells

Abstract: These findings suggest that ZFX plays an important role in breast cancer development and could be a potential therapeutic target for breast cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
29
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(33 citation statements)
references
References 23 publications
4
29
0
Order By: Relevance
“…We further revealed that ZFX expression was strongly associated with several clinicopathological factors in the tongue SCC specimens. Consistent with a previous study (20), we confirmed that ZFX expression was positively correlated with tumor grade and TNM classification of the tongue SCC, suggesting that ZFX overexpression was essential for the progression of tongue SCC. In addition, we revealed that ZFX overexpression was more frequent in male patients than that in female patients, suggesting a strong association between ZFX upregulation and gender.…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…We further revealed that ZFX expression was strongly associated with several clinicopathological factors in the tongue SCC specimens. Consistent with a previous study (20), we confirmed that ZFX expression was positively correlated with tumor grade and TNM classification of the tongue SCC, suggesting that ZFX overexpression was essential for the progression of tongue SCC. In addition, we revealed that ZFX overexpression was more frequent in male patients than that in female patients, suggesting a strong association between ZFX upregulation and gender.…”
Section: Discussionsupporting
confidence: 80%
“…Consistent with the results that ZFX knockdown caused cell cycle arrest in tongue SCC cell lines, previous studies showed that ZFX knockdown could inhibit the expression of cell cycle factors such as cyclin D1 and B1 in multiple types of cancer (18,20,21). Studies also found that ZFX depletion enhanced the expression of apoptotic factors including bax, caspase 1, 3 and 9 or inhibited the expression of anti-apoptotic factor such as bcl-2 in diverse cancers (12)(13)(14)18,20,21), which may account for the ZFX knockdown-induced cell apoptosis. Thus, it is quite possible that these mechanisms also function in tongue SCC, and further investigations are urgently needed to elucidate the mechanisms associated with ZFX-mediated tongue SCC development.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations